Antidepressant use and risk of epilepsy and seizures in people aged 20 to 64 years: cohort study using a primary care database - Hill, Trevor; Coupland, Carol; Morriss, Richard K.; Arthur, Antony; Moore, Michael; Hippisley-Cox, Julia (BioMed Central, 2015)
Background: Epilepsy is a serious condition which can profoundly affect an individual’s life. While there is some evidence to suggest an association between antidepressant use and epilepsy and seizures it is conflicting and not conclusive. Antidepressant prescribing is rising in the UK so it is important to quantify absolute risks with individual antidepressants to enable shared decision making with patients. In this study we assess and quantify the association between antidepressant treatment and the risk of epilepsy and seizures in a large cohort of patients diagnosed with depression aged between 20 and 64 years.